2022
DOI: 10.1111/cas.15287
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A 1 induces suppressive neutrophils through the Toll‐like receptor 2–mediated signaling pathway to promote progression of breast cancer

Abstract: Immune inflammation plays a key role in breast cancer development, progression, and therapeutic efficacy. Neutrophils are crucial for the regulation of the suppressive tumor microenvironment and are associated with poor clinical survival. However, the mechanisms underlying the activation of suppressive neutrophils in breast cancer are poorly understood. Here, we report that breast cancer cells secrete abundant serum amyloid A 1 (SAA1), which is associated with the accumulation of suppressive neutrophils. High … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
(103 reference statements)
2
17
0
Order By: Relevance
“…Neutrophils could create an immunosuppressive tumor microenvironment ( Figure 2 (B2)), primarily by the production of arginase [ 14 , 119 ], interleukin 10 (IL-10) [ 119 ], inducible nitric oxide synthase (iNOS) [ 119 ], and CCL17 [ 28 , 120 ]. In addition, TANs have been shown to express PD-L1 [ 82 , 121 , 122 , 123 ].…”
Section: Tumor–neutrophil Crosstalkmentioning
confidence: 99%
See 4 more Smart Citations
“…Neutrophils could create an immunosuppressive tumor microenvironment ( Figure 2 (B2)), primarily by the production of arginase [ 14 , 119 ], interleukin 10 (IL-10) [ 119 ], inducible nitric oxide synthase (iNOS) [ 119 ], and CCL17 [ 28 , 120 ]. In addition, TANs have been shown to express PD-L1 [ 82 , 121 , 122 , 123 ].…”
Section: Tumor–neutrophil Crosstalkmentioning
confidence: 99%
“…For example, Anselmi et al showed that human melanoma stem cells can activate and polarize neutrophil-like HL-60 cells toward the N2 phenotype via the production of polarizing factors such as TGF-β, IL-8, and IL-6 [ 142 ]. Niu et al showed that breast cancer cells modify neutrophils to an immunosuppressive phenotype by secreting serum amyloid A 1 (SAA1) [ 119 ]. SAA1 interacts with toll-like receptor 2 (TLR2) on neutrophils and promotes neutrophils to produce IL-10, arginase, and iNOS, indicating the immunosuppressive activities of SAA1-treated neutrophils.…”
Section: Tumor–neutrophil Crosstalkmentioning
confidence: 99%
See 3 more Smart Citations